Effect of glymphatic system function on cognitive function in patients with chronic kidney disease - Ko, Junghae; Park, Bong Soo; Heo, Chang Min; Yi, Jiyae; Lee, Dong Ah; Park, Kang Min (Frontiers in Neurology, 2024)
Objectives Studies have recently shown an alteration of the structural connectivity and a dysfunctional glymphatic system in patients with chronic kidney disease (CKD). In this study, we aimed to investigate the effects of the structural connectivity and glymphatic system on the cognitive function of patients with CKD. Methods We prospectively enrolled patients with CKD and healthy controls. The CKD group was divided into two regarding their cognitive function. All patients received brain magnetic resonance imaging, including diffusion tensor imaging (DTI). We calculated the measures of structural connectivity and diffusion tensor image analysis along the perivascular space (DTI-ALPS) index, a neuroimaging marker of the glymphatic system function, and compared the indices between groups. Results The mean clustering coefficient, local efficiency, and small-worldness index in patients with CKD were lower than those in healthy controls (0.125 ± 0.056 vs. 0.167 ± 0.082, p = 0.008; 1.191 ± 0.183 vs. 1.525 ± 0.651, p = 0.002; 0.090 ± 0.043 vs. 0.143 ± 0.102, p = 0.003; respectively). The DTI-ALPS index was lower in patients with CKD than in healthy controls (1.436 vs. 1.632, p < 0.001). Additionally, the DTI-ALPS index differed significantly between CKD patients with and without cognitive impairment. Notably, this index was lower in patients with CKD and cognitive impairment than in patients without cognitive impairment (1.338 vs. 1.494, p = 0.031). However, there were no differences of the structural connectivity between CKD patients with and without cognitive impairment. Conclusion We found lower DTI-ALPS index in patients with CKD, which could be related with glymphatic system dysfunction. Moreover, those with cognitive impairment in the CKD group had a lower index than those without, indicating a link between the glymphatic system function and cognitive function.